2014
DOI: 10.1002/ppul.23145
|View full text |Cite
|
Sign up to set email alerts
|

Hyperventilation syndrome in adolescents with and without asthma

Abstract: The prevalence of symptoms indicative of HVS in an unselected population of adolescents was relatively high. Symptoms were more common in girls and in subjects with asthma, and there was a significant effect of asthma activity on the probability of suffering from HVS. Further studies need to be performed in order to validate a screening tool for HVS in both adolescents and asthmatic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
5
17
1
1
Order By: Relevance
“…In this service evaluation, the prevalence of DB symptoms (NQ score ≥ 23) was 35%, which is higher than the 25.8% prevalence previous research has found . This may be due to our targeted cohort that was referred to physiotherapy based on a suspicion of DB.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this service evaluation, the prevalence of DB symptoms (NQ score ≥ 23) was 35%, which is higher than the 25.8% prevalence previous research has found . This may be due to our targeted cohort that was referred to physiotherapy based on a suspicion of DB.…”
Section: Discussionsupporting
confidence: 91%
“…This may be due to our targeted cohort that was referred to physiotherapy based on a suspicion of DB. Nevertheless, our findings support previous work that DB may be a clinically relevant comorbidity in pediatric asthma. High NQ scores (≥23) can be associated with non‐DB symptoms, for example, anxiety or stress, however, in this service evaluation it predominately correlated with an observed DB pattern.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations